Psychological Capital and its Relationship with Quality of Work Life among University Faculty Members (The International Journal of Educational Sciences and Arts, 2026)
Objectives: This study examined the level of psychological capital among university faculty members and its relationship with quality of work life within the context of the contemporary academic work environment. It also aimed to identify the relative contribution of psychological capital dimensions to quality of work life, as well as to explore differences according to selected demographic and professional variables.Methodology: A descriptive correlational design was employed due to its suitability for the study objectives. Data were collected using the Psychological Capital Questionnaire (PCQ) and a Quality of Work Life Scale, both of which demonstrated acceptable validity and reliability indicators.Sample: The study sample consisted of 160 faculty members from various academic ranks and disciplines across universities. Measures: Psychological capital was measured across four dimensions: self-efficacy, hope, optimism, and resilience. Quality of work life was assessed through dimensions related to work environment, institutional support, professional growth, and job satisfaction.Results: The results indicated that faculty members exhibited high levels of psychological capital and a generally high level of quality of work life. A strong, statistically significant positive correlation was found between psychological capital and quality of work life. Among the dimensions of psychological capital, self-efficacy and resilience emerged as the most influential predictors of quality of work life. The findings also revealed that academic work pressures were more negatively perceived among individuals with lower psychological capital, whereas higher psychological resources were associated with better occupational adjustment and greater job satisfaction.
Keywords: Psychological Capital; Quality of Work Life; Faculty Members